THE EFFECT OF ADOPTING KNOWLEDGE MANAGEMENT SYSTEM ON EMPLOYEE PERFORMANCE - Fajar Muttaqi (Scientific Journal of Information System, 2024)
There has been a shift in the needs of people and organizations that were originally material needs, now they are information needs. Especially the current workers, showing that 70% of workers there are knowledge workers and make knowledge the most useful resource at present. This study uses a quantitative approach with knowledge management independent variables consisting of people, knowledge sharing and technology and the dependent variable, namely employee performance. Sample was done by random sampling methods and sampling proportional technique, and the total sample produced was 70 people. The test uses validity, reliability and data analysis tests using ANOVA.